The Encyclopedia of Ancient History 2023
DOI: 10.1002/9781444338386.wbeah15129.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Middle Kingdom, Egypt

Abstract: The Middle Kingdom was regarded in later periods of Ancient Egypt as the country's “classical” age. Its literature and art works served as a model for the New Kingdom and Late Period and its language was still used for the latest hieroglyphic inscriptions in the Roman Period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…The temporal framework developed for this research is based on the chronology suggested on the Digital Egypt for Universities website, a learning and teaching resource developed by the University College London (UCL) [3]. The complete set of temporalities was established as follows: sites are defined into temporal brackets of human occupation predominantly identified by pottery sherds, soil sedimentation analysis or architectural features identified during field surveys or published archaeological reports.…”
Section: Temporal Coveragementioning
confidence: 99%
“…The temporal framework developed for this research is based on the chronology suggested on the Digital Egypt for Universities website, a learning and teaching resource developed by the University College London (UCL) [3]. The complete set of temporalities was established as follows: sites are defined into temporal brackets of human occupation predominantly identified by pottery sherds, soil sedimentation analysis or architectural features identified during field surveys or published archaeological reports.…”
Section: Temporal Coveragementioning
confidence: 99%